Comparison of in vitro Efficacy of Quinopristin /Dalfopristin, Linezolid and Vancomycin for Methicillin Resistant Staphylococcus Aureus - Arshad, Faiqa; Javed, Iffat; Mustafa, Tajammal; Mushtaq, Sohaila (International Journal of Pathology, 2018)
Objectives: To compare the in vitro activity of quinopristin/dalfopristin, linezolid and vancomycin bydetermining their minimum inhibitory concentrations (MICs) for methicillin-resistant Staphylococcusaureus (MRSA) isolated from various clinical samples received from LGH, Lahore.Study Design : Comparative StudyPlace and Duration of Study: Pathology Department, Post Graduate Medical Institute, Lahore fromFebruary 2013 to October 2013.Methodology: The MIC of quinopristin/dalfopristin, linezolid and vancomycin for 50 MRSA strainswere determined by using E-test strips (AB Biodisk, Biomeurix) and results were interpreted accordingto clinical and laboratory standards institute (CLSI) guidelines.Results: All the isolates showed 100% susceptibility to linezolid and quinopristin/dalfopristin and currentlyno resistant strain was found for these drugs. Quinopristin/dalfopristin showed lowest MICvalues than Linezolid and vancomycin.Conclusion: The study provided the in vitro information in establishing the role of linezolid andquinopristin/dalfopristin as an alternative to vancomycin for the treatment of serious MRSA infections.It also gives information regarding linezolid and quinopristin/dalfopristin as the best therapeutic optionfor the treatment of hVISA, VISA and VRSA.